15-Deoxy-Δ12,14-Prostaglandin J2 Inhibits Tissue Factor Expression in Human Macrophages and Endothelial Cells: Evidence for ERK1/2 Signaling Pathway Blockade - Eligini, S.; Banfi, C.; Brambilla, M.; Camera, M.; Barbieri, S. S.; Poma, F.; Tremoli, E.; Colli, S. (Thrombosis and Haemostasis, 2002)
Basic and clinical evidence has provided insight into the molecular events that link inflammation and coagulation. Increased expression of tissue factor (TF) by circulating and vascular cells has been indicated as responsible for the thrombotic complications associated with acute and chronic inflammation. TF is indeed inducible in circulating and vascular cells by cytokines and bacterial lipopolysaccharide (LPS) and its expression triggers the coagulation. The cyclopentenone prostaglandins are naturally occurring prostaglandin D2 (PGD2) derivatives that comprises prostaglandin J2 (PGJ2) and its metabolites Δ12-PGJ2 and 15-deoxyΔ12, 14-prostaglandin J2 (15d-PGJ2). These compounds, detected in vivo in a later phase of the inflammatory response, are characterized by anti-inflammatory activity and participate to the resolution of inflammation. We have here investigated the effect of 15d-PGJ2 on TF expression in human macrophages and endothelial cells (HUVEC). Our results indicate that 15d-PGJ2 down-regulates LPSand TNFα-induced TF activity, protein and mRNA through inhibition of TF gene transcription. The effect of 15d-PGJ2 is targeted to the NF-κB/I-κB pathway and to the mitogen activated protein kinase ERK1/2. A role of PPARγ activation in TF inhibition by 15d-PGJ2 was excluded. We conclude that 15d-PGJ2 negatively affects TF expression in macrophages and endothelial cells through a PPARγ-independent mechanism. This down-regulation may be crucial to limit excessive blood clotting activation in immuno-inflammatory diseases.
Keywords: Cyclopentenone prostaglandins; tissue factor; inflammation; thrombosis; macrophages; endothelial cells